2013
DOI: 10.1038/modpathol.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous marginal zone lymphomas with plasmacytic differentiation show frequent IgG4 expression

Abstract: The expression of IgG4 in malignant B-cell lymphomas has only partially been studied. Recent reports described single cases of marginal zone lymphomas arising in the ocular adnexae that express IgG4. Moreover, a subset of dura-associated marginal zone lymphomas appear to express IgG4 as well. We investigated IgG4 expression in a more systematic manner in a large cohort of marginal zone lymphoma specimens derived from the archive of our institute. Overall, we examined 169 marginal zone lymphomas of various prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 32 publications
3
90
1
2
Order By: Relevance
“…These lymphomas are thought to be derived from the infiltrating IgG4-positive cells in patients with pre-existing IgG4-RD because they have background features such as dense fibrosis and a high serum level of IgG4 [10,17]. However, it is still controversial whether such IgG4-positive cells can clonally expand to form malignant lymphomas [18,19]. Brenner et al reported that 39 % of cutaneous marginal zone lymphomas immunohistochemically expressed IgG4 and concluded that there was little association between IgG4-producing lymphomas and IgG4-RD [19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These lymphomas are thought to be derived from the infiltrating IgG4-positive cells in patients with pre-existing IgG4-RD because they have background features such as dense fibrosis and a high serum level of IgG4 [10,17]. However, it is still controversial whether such IgG4-positive cells can clonally expand to form malignant lymphomas [18,19]. Brenner et al reported that 39 % of cutaneous marginal zone lymphomas immunohistochemically expressed IgG4 and concluded that there was little association between IgG4-producing lymphomas and IgG4-RD [19].…”
Section: Discussionmentioning
confidence: 97%
“…However, it is still controversial whether such IgG4-positive cells can clonally expand to form malignant lymphomas [18,19]. Brenner et al reported that 39 % of cutaneous marginal zone lymphomas immunohistochemically expressed IgG4 and concluded that there was little association between IgG4-producing lymphomas and IgG4-RD [19]. Since it is highly likely that this case of IgG4-producing marginal zone lymphoma occurred in a patient with IgG4-RD, a subset of IgG4-producing lymphomas might arise from pre-existing IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…2 Most noncutaneous MALT lymphomas express IgM, whereas PCMZLs usually express IgG, IgA, and IgE, 3 and a significant number of them express IgG4. 4 Rosai-Dorfman disease (RDD) (sinus histiocytosis with massive lymphadenopathy) is a rare, idiopathic histiocytic disorder involving lymph nodes and, in about one-fourth of the cases, other organs, including the skin, 5 and primary isolated cutaneous involvement has been considered a distinct entity. 6 An exaggerated immune response to an infectious agent or antigen has been proposed as the cause for the proliferation of histiocytes in RDD.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, a significant percentage of dural marginal zone lymphomas and cutaneous marginal zone lymphomas have been shown to produce IgG4 without a known association with IgG4-RD. 37,38 The association of IgG4-RD and lymphoma, as well as the significance of IgG4 production by lymphomas, both nodal and extranodal, will require additional and larger studies for clarification. 39,40 In the presence of increased IgG4-positive cells, the possibility of lymphoma or other malignancy needs to be excluded.…”
Section: Igg4-related Lymphadenopathymentioning
confidence: 98%